Tornando-se psicólogo clínico - Carneiro, Virgínia Teles (2006)
The present study discuss how non-graduated Psychology trainees live deeply the experience of becoming clinical psychologists, having as reference the interchange between a practical knowledge, anchored in the personal experience, and theoretical knowledge. The legitimation of this research is to evidence the necessity of reformulation in clinical psychologists formation, that go beyond the suggest ones for the curricular reforms. In other words, the contribution comes from showing the incongruence on the formation of a professional that treats, but when considering the formal and official institutes, is neglected. Existential phenomenology is the methodological reference for this research, using verbal reports as resource. Two respected education institutions, Universidade Federal da Paraíba / UFPB and Centro Universitário de João Pessoa / UNIPÊ, both located in João Pessoa PB, were used as scenery. Eight trainees from these institutions, which were already initiated in both clinical psychological practice and supervision, act as collaborators on this research. The field research occurs in two different moments: first, a discussion group was organized in each institution; second, individual interviews were performed with the trainees trying to authenticate what was revealed on group discussions. The harvested testimony indicates pertinent aspects for understanding the proposed objective: the evident split of lived experience that comes from the graduation course structure itself; the extension of supervision in clinical formation; the importance of practice on formation context; the urgent necessity of evaluating the psychologists formation